PENDIDIKAN KARAKTER BERBASIS TEKNOLOGI INFORMASI DI LKSA NURUL FALAH MOJOKERTO - Muchibbatul Lutfiyah; Rosichin Mansur; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Character Education aims to shape the child's personality through education, habituation and supervision. Character education of children is not always formed in the family environment, especially for children who live in an institution or orphanage. The Child Welfare Institution is an institution that functions to provide services, guidance and assistance to children. The orphanage / LKSA is an institution to shape the development of children who do not have a family or who do not live with their family. Orphanage or child social welfare institution is an institution aimed at child welfare for underprivileged children, orphans / orphans or neglected children. Information Technology is a tool to communicate by helping humans in creating, changing, storing, communicating, and disseminating information . In this era of globalization, information technology is developing very rapidly, especially in the field of character education. In private institutions, especially Islamic boarding schools or orphanages, they have begun to develop information technology, namely through the internet, especially in the Nurul Falah Welfare Institution, Mojokerto. This development aims to shape the characteristics of foster children so that they become individuals who have good morals and have skills in their respective fields.